Kinetics of thermal degradation of beet dyes (beta vulgares l) in aqueous medium - Silva, Tays Dias da; Silva , Herlane Miranda da; Rosas , Júlio Cesar Freitas; Ribeiro , Alan Bezerra; Costa , José de Ribamar Macedo (Seven Editora, 2023)
The betacyanin dyes present in beets (Beta vulgaris L) were extracted with water from lyophilized and pulverized beets, with a ratio of 50 g/1000 mL/10 minutes, at room temperature. The extract was separated by centrifugation at 3000 rpm/20 minutes. From the stock solution, dye solutions corresponding to the proportion of 5×10-3 gbeetroot mL-1 were prepared for the thermal degradation tests, in the temperature range of 30°C to 80°C, in a thermostatized bath, being monitored by absorption analysis in the ultraviolet-visible region, wavelength,  , 480 nm for betaxanthins and 537 nm for betakinanins, for 180 minutes. The degradation of the dye follows a kinetic of 1st order for homogeneous reactions, with 1 reagent and the constant reaction rate was 1.4×10-4 mg/h, the half-life time, t1/2, was 8.25 hours, at a temperature of 30°C for the betacyanin dye. The degradation process has an activation energy of 55.39 kJ/mol for betacyanin dye and 56.06 kJmol-1 for betaxanthin. After the time of the degradation test, the solution assumes a yellowish color associated with betalamic acid, the degradation product of betacyanin. DOI:https://doi.org/10.56238/alookdevelopv1-164